2016
DOI: 10.1177/0956462415627397
|View full text |Cite
|
Sign up to set email alerts
|

Infectious syphilis in women: what’s old is new again?

Abstract: The aim of this study was to examine trends in infectious syphilis epidemiology among women in Winnipeg, Canada. A descriptive study of syphilis among Winnipeg residents between 2003 and 30 June 2015 was undertaken. Adjusted rate ratios (ARR) and 95% confidence intervals (95%CI) from Poisson regression analyses are reported. Characteristics of men and women were compared using logistic regression, with adjusted odds ratios (AOR) reported. Between 2014 and 2015, the rate of syphilis was 1.7/100,000, representin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…Our results are conditional on the epidemiological context under study, and the relative impact of focused screening of MSM with prior syphilis may vary by the rates of reinfection in the region of interest. Relatedly, the syphilis epidemic in Winnipeg has evolved, making significant inroads into heterosexual populations26; further research is needed to understand the impact of focused screening of populations susceptible to reinfection on mixed or parallel syphilis epidemics.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are conditional on the epidemiological context under study, and the relative impact of focused screening of MSM with prior syphilis may vary by the rates of reinfection in the region of interest. Relatedly, the syphilis epidemic in Winnipeg has evolved, making significant inroads into heterosexual populations26; further research is needed to understand the impact of focused screening of populations susceptible to reinfection on mixed or parallel syphilis epidemics.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] However, more recently, increased notifications among non-MSM populations, particularly women, have been reported. 5,7,8 Japan, for instance, has seen an increase in syphilis notifications since 2013, with a substantial increase among both men who have sex with women (MSW) and women who have sex with men (WSM); between 2013 and 2016, cases increased from 304 to 1671 among MSW and 137 to 1077 among WSM. 9 Several studies have reported risk factors for syphilis among women, such as socioeconomic and education status and sexual behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Local jurisdictions during the syphilis elimination effort frequently faced different phases of STD epidemics across their respective jurisdictions, in much the same way as they do now. 1114 In some jurisdictions, for example, a target population with high endemic rates of gonorrhea and chlamydia can suddenly find itself in the throes of a spiking outbreak of syphilis. To be effective, a local health department can be called upon to mount a targeted out-break response while at the same time maintaining an ongoing program to address endemic diseases.…”
Section: Complications and Implicationsmentioning
confidence: 99%